The production of a Crimean-Congo haemorrhagic fever virus diagnostic antigen in plants - Atkinson, Richard (Department of Molecular and Cell Biology, 2016)
Crimean-Congo Hemorrhagic Fever (CCHF) is a highly infectious, life threatening disease, caused by the Crimean-Congo Hemorrhagic Fever Virus (CCHFV), a nairovirus that forms part of the Bunyaviridae family. CCHFV has a case fatality rate of approximately 40%. Current diagnostic methods for CCHFV involve the use of live virus antigen, requiring biosafety level 4 (BSL4) conditions for safe handling. The development of a safer diagnostic reagent for detection of this disease is therefore desirable. This project involves the development of a recombinant CCHFV nucleocapsid protein (NP). The nucleocapsid (NP) protein was expressed in Nicotiana benthamiana and purified using a 6x histidine-tag. The protein was then reacted against serum samples collected from confirmed CCHFV patients to determine its ability to detect IgG antibodies against CCHFV in human sera.